The Effect of Different Doses of Citronella Oil (Cymbopogon citratus) as Anesthetic for Prospective Tilapia Broodstock (Oreochromis niloticus) in Closed Transportation System - Aryanti, Astarini Shabrina; Harwanto, Dicky; Yuniarti, Tristiana (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Anesthesia of fish with citronella oil in a closed transportation system has never been tested on prospective tilapia broodstock. The broodstocks transportation activities are to ensure survival and keep the reproductive stages undisturbed and safe to the destination. This study aims to determine the effect and the best dose on anesthesia with citronella oil for prospective tilapia broodstock in closed transportation systems. The research was conducted on 27 April – 4 May 2021 at Fish Seed Hall Potrobangsan, Magelang. The test material used citronella oil with a fish density of 10 fish/6 liters per bag. The experimental design used was a completely randomized design with five treatments and three replications with doses of citronella oil, namely A (0 mL/L as control); B (0,05 mL/L), C (0,10 mL/L); D (0,15 mL/L); and E (0,20 mL/L). Fish were transported for 13 hours with artificial simulation. Parameters observed were fish behavior during anesthesia, time to faint and recover, survival, water quality, blood glucose, blood profile (erythrocytes, leukocytes and hemoglobin), Hepatosomatic Index and Gonadosomatic Index. Behavior during anesthesia showed that the operculum slowed down, response weakened and swimming balance was lost. Different dose of citronella oil had a significant effect on survival, blood glucose, erythrocytes, and leukocytes, but had no significant effect on hemoglobin, Hepatosomatic Index (HSI) and Gonadosomatic Index (GSI). The best dose of citronella oil was 0.10 mL/L with an average survival of 93.33%.Keywords: anesthesia, citronella, tilapia, broodstock, transportation